Rights Granted to an Insured Person Who Has a Work Accident and Rights Owners in the Event of the Death of the Insured in the Social Security System - Atanur Karaahmetoğlu (Sosyal Siyaset Konferansları Dergisi)
An insured person who has suffered an occupational accident faces both physical and mental damages and financial difficulties. For this reason, it is of great importance to offer legal protection to insured persons who have suffered work accidents. Therefore, every state has taken some legal steps to protect insured persons who have suffered work accidents, granting various rights to insured persons who were victims of work accidents, and the limits of these rights have been delineated. In Turkey, legal protection for insured persons who have suffered occupational accidents has been achieved with the entry into force of the Social Insurance and General Health Insurance Law No. 5510. In addition, SSGSSK (Law No. 5510) has provided legal protection to insured persons who have suffered work accidents and has set out the limits of the rights granted to such persons and the rights granted to the rights-holders in case of the death of the insured person. In this study, in line with the relevant articles of Law No. 5510 and decisions of the Supreme Court, a question was asked about the legal status of the insured who suffered an occupational accident: what were the rights of insured persons and of rights-holders in the event of the death of the insured?